Islamic Religious Education in Building Insight Multicultural - Sarbaini, Sarbaini; Kustati, Martin; Sepriyanti, Nana (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Islamic religious education (PAI) taught in madrasas and public schools is felt has not been one hundred percent successful in making students be tolerant and open towards other communities outside himself. This type of research is a systematic literature review which is carried out by collecting and accumulating research related to community-based total sanitation evaluation. The keywords used for literature searches;